Personality and language structure in two languages - Dixon, J. C.; Garcia-Esteve, Joel; Sigvartsen, Martha L. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The relation between personality and differential use of various grammatical structures was studied in a group of 162 Florida and 201 Puerto Rico college students of both sexes. The personality measures included the Internal-External Scale and an experimental scale adapted to this study, Attribution of Responsibility. The language measures were derived from (1) an adaptation of Semantic Differential technique to assess the active-potent dimension of meaning of first person subject and object pronouns, and (2) the use of 40 selected verbs with instructions to use these in making up 40 oral sentences which were recorded and later transcribed and analyzed according to various grammatical categories. No significant relation between personality measures and measures of grammatical or semantic structure was obtained.